31-(2c+4)=2(c+6)+c

Simple and best practice solution for 31-(2c+4)=2(c+6)+c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 31-(2c+4)=2(c+6)+c equation:


Simplifying
31 + -1(2c + 4) = 2(c + 6) + c

Reorder the terms:
31 + -1(4 + 2c) = 2(c + 6) + c
31 + (4 * -1 + 2c * -1) = 2(c + 6) + c
31 + (-4 + -2c) = 2(c + 6) + c

Combine like terms: 31 + -4 = 27
27 + -2c = 2(c + 6) + c

Reorder the terms:
27 + -2c = 2(6 + c) + c
27 + -2c = (6 * 2 + c * 2) + c
27 + -2c = (12 + 2c) + c

Combine like terms: 2c + c = 3c
27 + -2c = 12 + 3c

Solving
27 + -2c = 12 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
27 + -2c + -3c = 12 + 3c + -3c

Combine like terms: -2c + -3c = -5c
27 + -5c = 12 + 3c + -3c

Combine like terms: 3c + -3c = 0
27 + -5c = 12 + 0
27 + -5c = 12

Add '-27' to each side of the equation.
27 + -27 + -5c = 12 + -27

Combine like terms: 27 + -27 = 0
0 + -5c = 12 + -27
-5c = 12 + -27

Combine like terms: 12 + -27 = -15
-5c = -15

Divide each side by '-5'.
c = 3

Simplifying
c = 3

See similar equations:

| 722=485+b | | (5s-2t)-(2s-4t)= | | 7a=36*21 | | X+59+84+X+51=180 | | 128=-8(-2+2p) | | 42p-39=66p-87 | | 7-3d-5=-1+2d-12+d | | 247=-7(-1+8b)-4b | | a+25=-8 | | 3y-x=12 | | 7x+y=12 | | 4(x-4)+5=35-5x | | -14-2x=-4x+26 | | x-3/8=1/8 | | 2x+3=2(x-2) | | 138=n-216 | | 31-(2c+4)=2(c+6)c | | 5(2m+8)=100 | | 5x^2+30x+10=0 | | 16a+37-7a=46 | | 3x^2-3x-44=0 | | 15=2.3b | | 15k+2k=5k+6 | | 1a-4a=2a+1-5a | | 5n=3*21 | | 8(1+4n)=168 | | -11+3x=61 | | -6x-6(-5x-1)=150 | | -5h+11-9h=-227 | | 138=n-21b | | 11(9v+5)=-40+4v | | 2d-4=-4 |

Equations solver categories